2021
DOI: 10.1038/s41598-021-93633-7
|View full text |Cite
|
Sign up to set email alerts
|

Smoking accelerates renal cystic disease and worsens cardiac phenotype in Pkd1-deficient mice

Abstract: Smoking has been associated with renal disease progression in ADPKD but the underlying deleterious mechanisms and whether it specifically worsens the cardiac phenotype remain unknown. To investigate these matters, Pkd1-deficient cystic mice and noncystic littermates were exposed to smoking from conception to 18 weeks of age and, along with nonexposed controls, were analyzed at 13–18 weeks. Renal cystic index and cyst-lining cell proliferation were higher in cystic mice exposed to smoking than nonexposed cystic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Cigarette smoking caused abnormal physiological indices (such as reduced body weight, blood lipid levels, and food intake) that resulted in hepatocellular damage, abnormalities in the liver transcriptome during lipid metabolism, and disruption of the gut microbiota in mice [22][23][24]. Moreover, other fndings showed the renal function of mice was negatively afected by exposure to cigarette smoking, which led to an acceleration of renal fbrosis and cystic development as well as a physiological reduction in glomerulus fltration rate [25,26]. Exposure to cigarette smoke increases intestinal mucosal disruption, intestinal barrier dysfunction, oxidative stress, apoptosis, and tight junction component dysregulation [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking caused abnormal physiological indices (such as reduced body weight, blood lipid levels, and food intake) that resulted in hepatocellular damage, abnormalities in the liver transcriptome during lipid metabolism, and disruption of the gut microbiota in mice [22][23][24]. Moreover, other fndings showed the renal function of mice was negatively afected by exposure to cigarette smoking, which led to an acceleration of renal fbrosis and cystic development as well as a physiological reduction in glomerulus fltration rate [25,26]. Exposure to cigarette smoke increases intestinal mucosal disruption, intestinal barrier dysfunction, oxidative stress, apoptosis, and tight junction component dysregulation [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CY mice had to be analyzed at a significantly higher age, to have enough time to present an adequate cystic phenotype. In this context, we chose to work with 10–12-week-old CY and NC mice, as well as 10–12-week-old HT and WT animals; CY animals display a mild to moderate renal cystic phenotype which has been shown to be associated with preserved renal function even at ages of a few more weeks than the age range used in the current study 30 , 31 . The other reason, which supported/validated our decision, was the finding that the housekeeping gene expression profiles detected in CO mice (control wild-type animals with 15 days of life) did not significantly differ from the other controls WT and NC ( PPIA with median Cts lying between 16 and 17, HPRT between 21–24 and ACTB between 24–27).…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study demonstrated that alcohol abuse increased kidney fibrosis through SMAD7 downregulation [ 124 ]. Smoking was associated with increased renal fibrosis in autosomal dominant polycystic kidney disease subjects [ 125 ]. Obesity is another factor involved in renal damage; therefore, some authors recommend bariatric surgery to improve kidney function [ 126 ].…”
Section: Therapeutic Potential In Renal Fibrosismentioning
confidence: 99%